Association of dietary insulinaemic potential and odds of non‐alcoholic fatty liver disease among adults: A case–control study. Issue 5 (15th February 2021) - Sohouli, Mohammad Hassan; Sayyari, Ali Akbar; Lari, Abolfazl; Nameni, Ghazaleh; Lotfi, Mojtaba; Fatahi, Somaye; Saneie, Solaleh; Găman, Mihnea‐Alexandru; Moodi, Farzan; Raee, Pourya; Aghamiri, Shahin; Rayi, Appaji; et al.
Abstract: Background: Hyperinsulinaemia is considered as a major risk factor for the development of a myriad of chronic diseases. We examined the association between the dietary insulinaemic potential and the odds of non‐alcoholic fatty liver disease (NAFLD) among Iranian adults. Methods: After being subjected to a liver ultrasound, 166 patients with NAFLD and 200 controls were included in the study. The dietary intakes and the physical activity levels of the participants were evaluated using a validated semi‐quantitative food frequency questionnaire and the International Physical Activity Questionnaire (short IPAQ), respectively. The insulinaemic potential of the diet was assessed by computing the scores of the Empirical Dietary Index for Hyperinsulinemia (EDIH) and the Empirical Dietary Index for Insulin Resistance (EDIR). Results: Compared with the control subjects, patients with NAFLD were significantly older; had higher values for body mass index, fasting blood sugar, triglycerides, low‐density lipoprotein cholesterol, total cholesterol and alanine transaminase; and were more likely to smoke. Moreover, NAFLD patients had significant lower levels of high‐density lipoprotein cholesterol and were less likely to perform physical activity. The risk of NAFLD was higher in the individuals in the highest tertile of the EDIH (odds ratio [OR] = 2.79; 95% confidence interval [CI] = 1.32–5.90; p  value for trend < 0.05) and EDIR (OR = 2.42; 95% CI = 1.22‐4.79; p  value for trend < 0.05) compared to those in the lowest tertile of these scores. Conclusions: Our study indicates that a higher dietary insulinaemic potential is associated with an increased risk of NAFLD. Abstract : Hyperinsulinaemia is considered as a major risk factor in the development of a myriad of chronic diseases. The results of the present study indicate that a higher dietary insulinaemic potential is associated with an increased risk of non‐alcoholic fatty liver disease. Further prospective studies are needed to confirm these findings.